PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT SETELAH ABAD KE SEMBILAN BELAS - Razali Abdullah (SI-MEN, 2016)
The main purpose of this study was to investigate the level of economic growth and human welfare using panel data which derived by Angus Maddison (1995) for 56 countries worldwide. This research was conducted by using descriptive qualitative approach in order to find out the real data of economic growth that is the level of per capita real output individual country respectively. The result of the research shows that there is a great variety level of per capita real output growth consecutively among them by the year 1820 throughout 1992. The more freedom people have to make choices, the higher their welfare is likely to be. Freedom should be correlated with per capita real GDP and can thus serve an alternative measure of human welfare in place of GDP.Therefore, economic can not grow well without structure change accordingly.